2020
DOI: 10.1111/liv.14634
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C treatment uptake among people who inject drugs in the oral direct‐acting antiviral era

Abstract: Background: Increased uptake of hepatitis C virus (HCV) treatment among people who inject drugs (PWID) will be critical to achieve HCV elimination goals. There are limited data on HCV treatment uptake among PWID recruited from communitybased settings in the HCV direct-acting antiviral (DAA) era. Methods: We analysed data from PWID with HCV newly recruited into the Baltimore, Maryland-based AIDS Linked to the IntraVenous Experience (ALIVE) cohort between 2015 and 2018. We characterized the HCV care continuum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
(59 reference statements)
0
18
1
1
Order By: Relevance
“…The rate of uptake of antiviral treatment among PWID before the DAA era was reported to be low, probably due to poor tolerability and lack of efficacy, 22,23 although it is increasing with DAA treatment in the United States. 24 In contrast, our study showed that the overall treatment rate was higher among PWID than among non-PWID, especially in the pre-DAA era. In the pre-DAA era, old age and E p u b a h e a d o f p r i n t comorbidities might have deterred interferon-based therapy, so that the PWID group with younger age and less comorbidities treated more than the non-PWID group.…”
Section: E P U B a H E A D O F P R I N Tcontrasting
confidence: 74%
See 1 more Smart Citation
“…The rate of uptake of antiviral treatment among PWID before the DAA era was reported to be low, probably due to poor tolerability and lack of efficacy, 22,23 although it is increasing with DAA treatment in the United States. 24 In contrast, our study showed that the overall treatment rate was higher among PWID than among non-PWID, especially in the pre-DAA era. In the pre-DAA era, old age and E p u b a h e a d o f p r i n t comorbidities might have deterred interferon-based therapy, so that the PWID group with younger age and less comorbidities treated more than the non-PWID group.…”
Section: E P U B a H E A D O F P R I N Tcontrasting
confidence: 74%
“…The rate of uptake of antiviral treatment among PWID before the DAA era was reported to be low, probably due to poor tolerability and lack of efficacy [ 22 , 23 ], although it has increased with DAA treatment in the United States [ 24 ]. In contrast, our study showed that the overall treatment rate was higher among PWID than among non-PWID, especially in the pre-DAA era.…”
Section: Discussionmentioning
confidence: 99%
“…Internationale Studien zeigen, dass z. B. innovative Rekrutierungsstrategien mit geschulten Peers [26], Belohnungsanreize [27] oder Versorgungsmodelle mit integrierter Testung, Diagnose und Versorgung [28] geeignet sein können, um die Inanspruchnahme von HCV-Test-und -Behandlungsangeboten bei Menschen mit injizierendem und anderen Drogenkonsumformen zu erhöhen.…”
Section: Diskussionunclassified
“…, 2020). Models of integrated care delivery for opioid use disorders (OUPs), HCV, and HIV are being studied and early results find high acceptance for colocated care among practitioners (Falade-Nwulia et al, 2020;Rich et al, 2018).…”
mentioning
confidence: 99%
“…Using approaches modeled on Extension for Community Healthcare Outcomes (Project ECHO), academic medical centers have trained and coached rural primary care providers to prescribe HCV treatment in rural areas (North Carolina Carolina Hepatitis Academic Mentorship Program [CHAMP] Program, 2020). Models of integrated care delivery for opioid use disorders (OUPs), HCV, and HIV are being studied and early results find high acceptance for colocated care among practitioners (Falade-Nwulia et al, 2020; Rich et al, 2018). Recently, a large, national randomized, pragmatic trial showed that PWID could be successfully cured of HCV when treatment was delivered in opioid treatment clinics and community health centers (Litwin, Jost, et al, 2019).…”
mentioning
confidence: 99%